Port site hernia following transperitoneal laparoscopic pyeloplasty - Ashraf F. Hefny; Hamda Musafir; Asma Al Shamsi; Sherif A. Fathi (Radiology Case Reports)
Most surgical procedures in the past were performed through large incisions. Advancement of laparoscopic surgery has led to smaller incisions and reduction in most of the incision-related complications. However, laparoscopic surgery has its own complications. One of these complications is port site hernia which is an uncommon complication that can cause significant morbidity and requires an additional surgical procedure. Port site hernia following transperitoneal laparoscopic pyeloplasty is extremely rare. Herein, we present such a case in which the patient was managed conservatively. To our knowledge this is the first reported case in literature.